Tell Me Friends : Contemporary Stories and Plays of Tanzania. - Osaki, Lilian (Mkuki na Nyota Publishers, 2009)
This third volume of Tell Me, Friends collects stories and plays written by students and staff at the University of Dar es Salaam between 2006 and 2008. The stories in the collection are: ""Our Man"" by Saida Yahya-Othman; ""The Window Seat"" by Benjamin Branoff; ""The Concealed Project"" by Zuhura Badru; ""The Total Crisis"" by Simon Mlundi; and ""Testimony"" by Emmanuel Lema. The plays are: ""The Monster"" by Anna Chikoti; ""Love is ... "" by Kimberly McLeod; ""A Tanzanian Rooftop"" by Benjamin Branoff; ""Judges on Trial"" by Frowin Paul Nyoni; ""The Route to Success"" by Yunus Ng'umbi; and ""